The MobIS-Challenge 2019 - A Report on the WI-2019-Workshop on Model-Based Compliance in Information Systems - Baier, Stephan; Dunzer, Sebastian; Fettke, Peter; Houy, Constantin; Matzner, Martin; Pfeiffer, Peter; Rehse, Jana Rebecca; Scheid, Martin; Stephan, Sebastian; Stierle, Matthias; Willems, Brian (Enterprise Modelling and Information Systems Architectures - International Journal of Conceptual Modeling, 2020)
Information systems (IS) can significantly support the organization of business processes. However, the proceeding digitalization of processes can also lead to an increasing organizational complexity and the need to more intensely investigate the adherence to external or internal compliance rules. Process-related data from IS and underlying process models can, however, also contribute to an effective compliance checking. This paper summarizes the motivation, the setup, the data set and the results of the 2019 MobIS-Challenge which was conducted as a workshop at WI 2019 in Siegen, Germany. Results submitted to the challenge are presented in detail and directions for future work are discussed.<br
Keywords: GRC; Governance; Risk and Compliance; BPM; Business Process Management; Process Mining; Data Set; DCR; Declarative; Dynamic Condition Response Graph